Assessment of Tax Compliance Costs for Businesses in the Republic of Tajikistan - International Finance Corporation (Washington, DC, 2018)
The principal outcome of the tax reform implemented in recent years in the Republic of Tajikistan is the reduction of administrative burden on the private sector associated with compliance with tax legislation through simplified tax procedures and less time required to pass these procedures. The International Finance Corporation (IFC), a member of the World Bank Group, is the largest global development institute, which is focused on support to the private sector in emerging economies. The objective of the IFC Central Asia Tax Project is to improve compliance with mandatory requirements of tax legislation through better transparency and simplification of tax administration procedures. IFC through its technical assistance tax reforms projects, has conducted a series of studies, which allow to monitor the tax system reforming processes in Tajikistan. The main goal of the studies was a periodic assessment of time and costs of taxpayers in Tajikistan to comply with the mandatory requirements of the tax legislation. As part of the study, three rounds of measurements were performed, where the tax administration costs of the Tajik taxpayers were assessed at a regular time span - in 2012, 2014, and 2016. This report presents the results of all three rounds of business environment surveys in the area of tax regulation. It includes the estimates of tax accounting costs of taxpayers in Tajikistan in 2012, 2014, and 2016.